On the Lateral Support of Inelastic Columns - Pincus, George (Engineering Journal, 1964)
The failure buckling load of centrally loaded columns with a high slenderness ratio is given by the Euler elastic buckling formula. An idealized column model may be used to find the buckling load of a centrally loaded column. A linear spring may be added to such a model to represent the effect of lateral support on the column. It is shown that inelasticity at failure requires a greater amount of (or stiffer) lateral support to reach a given load than that based on elastic conditions at failure. This phenomenon must be recognized by designers who assume lateral support as fully effective when it meets an arbitrary criterion or rule of thumb.